NILAI-NILAI BUDAYA & KARAKTERISTIK LITERASI BUDAYA DAN KEWARGANEGARAAN: Penelitian R&D - Faizah, Lailatul; Al-Fajri, Muhammad; Wati, Ni'ma; Muharyati, Sitti Nur Annisa; Nawir, Muhammad; Muhajir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Cultural and civic literacy plays an essential role in fostering the character development of elementary school students amid the challenges of globalization and rapid digital transformation. This study aims to analyze the implementation, strengthening strategies, and challenges of cultural and civic literacy based on findings from previous studies. This research employed a literature review method by analyzing 20 scientific articles published between 2021 and 2026, which were retrieved from Google Scholar based on their relevance to the research topic. The data were analyzed descriptively through the processes of identification, selection, classification, and synthesis of research findings. The results indicate that the implementation of cultural and civic literacy is carried out through integration into classroom learning, school culture, co-curricular and extracurricular activities, as well as the utilization of local culture as a learning resource. The most widely adopted strengthening strategies include curriculum integration, the use of innovative learning media, collaboration among schools, families, and communities, and the appropriate use of digital technology. These practices contribute to strengthening students' character by promoting tolerance, nationalism, social awareness, critical thinking, and responsibility as citizens. However, the review also reveals that studies focusing on learning models integrating cultural literacy, civic literacy, and digital literacy remain limited. Therefore, further research is needed to develop more innovative and contextual learning models to support character education in elementary schools.